The Effect of Giving Lime Soy Sauce on Reducing the Intensity of Non-Pnemonia Coughs in Pre-School Children at PMB Anik Susilawati Sidodadi Gedangan Malang - Iif Wahyu Kusumawati; Anik Sri Purwanti; Sulistiyah, Sulistiyah; Reny Retnaningsih (Sean Institute, 2023)
The population in this study were all pre-school children with coughs not pneumonia who were examined at PMB Atik Susilawati during April - May 2023 in Sidodadi village, Gedangan, Malang. Results: Wilcoxon Signed Test analysis obtained a Sym Sig 2 value 0.000 <0.05 in meaning that P<0.05, so the hypothesis (Ha) in this study is accepted where it exists. Conclusion: there is a significant effect between before and after the treatment of giving lime soy sauce to pre-school children.